Ownership Concentration and other Determinants of Covenants in Debt Contracts of Brazilian Publicly Listed Firms - Tatiana Albanez; Rafael Felipe Schiozer (BBR: Brazilian Business Review)
This article investigates whether the concentration of stock ownership affects the presence and intensity of covenants in the debt contracts of companies listed on the B3 stock exchange in the 2007-2018 period. We also present an overview of the presence and breach of covenants by these firms. For this purpose, we manually analyzed more than 4,000 explanatory notes for the firms’ financial statements regarding loans and financing and then applied linear and nonlinear regression models. We found that greater ownership concentration is associated with higher likelihood of the presence of covenants, corroborating the role of the ownership structure as a substitute governance mechanism that allows for aligning interests and reduces the need for using covenants. The results are useful to managers, creditors, and shareholders, by showing which characteristics are determinants of the use of covenants, supporting management of factors that can reduce their occurrence, and bring greater flexibility to the corporate decision-making process, directly maximizing the value to shareholders.